A Quasi Experiment on Outcome of Mirabegron and Solifenacin in the Treatment of Primary Over Active Bladder in A Tertiary Hospital in Dhaka, Bangladesh - Sarkar, Md Israfil; Islam, Mohammad Saiful; Azad, Abdul Kalam; Alam, Rashedul; Alam, Mahabuba; Gupta, Sudip Das; Hoque Rabbani, Md Rezwanul; Islam, Md Mozharul (Sir Salimullah Medical College Journal, 2022)
Background: Overactive bladder (OAB) syndrome is a common symptom complex that affects millions of people worldwide, with an increasing prevalence with increased age in primary overactive bladder. Objective: The study was done to find out the efficacy and outcome of Mirabegron and solifenacin on primary overactive bladder. Methodology : This study was a quasi-experimental study conducted on 100 study population (Group A-50 Group B-50) in Urology Outpatient Department, Sir Salimullah Medical College Mitford Hospital, Dhaka from July 2017 to December 2018. Study population were total 100 men and women aged at least 18 & up to 60 years (Group A -50 and Group B-50) with persistent primary overactive bladder (OAB) symptoms for 3 months or more were enrolled in this study. Patients were eligible for the study who were able to give a written informed consent before starting the intervention & was also able to complete a voiding diary. Patients were recruited at the urology outpatient department, SSMCMH, Dhaka and were selected by the following inclusion and exclusion criteria. A data sheet was completed for each patient which included particulars of the patient, history, examination findings and baseline investigations. Half of the patients were enrolled in each group. Mirabegron group was experimental group and Solifenacin group was control group. Cases of Mirabegron group was given once daily dose of Mirabegron 25 mg and Solifenacin group was also given single dose of Solifenacin succinate 5 mg, at for 12 weeks. Result: The result of age distribution of the study patients belonged to age 31-40 years in group A (Mirabegron 25 mg) 21(42.0%) and 16(32.0%) in group B (Solifenacin 5 mg). The mean voided volume of each micturation at 12 week of treatment was more increased in group A (Mirabegron 25 mg) than group B (Solifenacin 5 mg). The mean change in micturition frequency per 24 hours, episodes of urgency per 24 hours, urge incontinence episodes per 24 hours and nocturia episodes per 24 hours were statistically significant (p<0.05) between group A (Mirabegron 25 mg) and group B (Solifenacin 5 mg). Conclusion The study shows that Mirabegron is more effective than Solifenacin in the treatment of primary over active bladder and can be used in without organic and pathological diseases of urinary bladder Sir Salimullah Med Coll J 2022; 30: 55-60